2021
DOI: 10.1136/sextrans-2021-055013
|View full text |Cite
|
Sign up to set email alerts
|

Accessing needed sexual health services during the COVID-19 pandemic in British Columbia, Canada: a survey of sexual health service clients

Abstract: ObjectivesWe assessed COVID-19 pandemic impacts on accessing needed sexual health services, and acceptability of alternative service delivery models, among sexual health service clients in British Columbia (BC), Canada.MethodsWe administered an online survey on 21 July–4 August 2020 to clients using a provincial STI clinic or internet-based testing service, GetCheckedOnline, in the year prior to March 2020. We used logistic regression to identify factors associated with having unmet sexual health needs (ie, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 17 publications
3
20
1
Order By: Relevance
“…We used established recruitment methods to invite STI clinic clients who had previously consented to be contacted for research to participate in this survey (∼20% of all clinic clients). [13] , [14] A generic e-mail invitation to the survey was sent to all consenting clients who visited the clinic between June 1, 2019 and May 31, 2022, with a link to the online survey landing page which outlined the additional eligibility criteria (age 16 years and older and able to complete a survey in English) and provided the information needed for informed consent. Proceeding to start the survey was considered provision of informed consent, and all participants starting the survey were offered the opportunity to enter a prize draw for a $200 VISA gift card.…”
Section: Methodsmentioning
confidence: 99%
“…We used established recruitment methods to invite STI clinic clients who had previously consented to be contacted for research to participate in this survey (∼20% of all clinic clients). [13] , [14] A generic e-mail invitation to the survey was sent to all consenting clients who visited the clinic between June 1, 2019 and May 31, 2022, with a link to the online survey landing page which outlined the additional eligibility criteria (age 16 years and older and able to complete a survey in English) and provided the information needed for informed consent. Proceeding to start the survey was considered provision of informed consent, and all participants starting the survey were offered the opportunity to enter a prize draw for a $200 VISA gift card.…”
Section: Methodsmentioning
confidence: 99%
“…Since the COVID-19 pandemic began, commentaries (Hussein 2020;Aly et al 2020;Kumar, Malviya, and Sharma 2020;Hall et al 2020) and empirical studies on the impacts of COVID-19 on SRH have emerged (Gilbert et al 2021;Bolarinwa 2021;Lewis et al 2021a;Both, Castle, and Hensen 2021;Yarger et al 2021;Endler et al 2021;Balachandren et al 2022;Steiner et al 2021). Some studies, such as ours, found that access to contraception became difficult during lockdowns (Balachandren et al 2022), and others focused specifically on the impact on adolescents and young people (Lewis et al 2021a;Both, Castle, and Hensen 2021;Yarger et al 2021;Steiner et al 2021).…”
Section: Discussionmentioning
confidence: 89%
“… 2020 ) and empirical studies on the impacts of COVID‐19 on SRH have emerged (Gilbert et al. 2021 ; Bolarinwa 2021 ; Lewis et al. 2021a ; Both, Castle, and Hensen 2021 ; Yarger et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many routine primary care visits have been deferred and primary care services have been operating at reduced capacity throughout the pandemic. While availability of services strongly determines access, other factors, such as individuals' comfort in accessing health services during a pandemic and messaging around limiting interactions with health services, likely played a role as well ( Gilbert et al., 2021 ; Rawaf et al., 2020 ). As patients return to their routine care, FPs' identification of the health impacts on communities experiencing marginalisation, including increased rates of infections and late diagnoses of terminal illnesses, suggests that how ‘essential care’ is framed, including what is deemed ‘essential’, during a pandemic can have harmful consequences.…”
Section: Discussionmentioning
confidence: 99%